Tulsi plant at the entrance of the home - Mumbai Archive Project Team (Jio Institute, 2024)
The presence of a Tulsi plant at the entrance of the home is believed to ward off evil spirits and negative energies and provide spiritual protection to the household. Even the soil around the plant is considered holy.